Indonesian Netizens' Emotive Language in Responding to YouTube Posts: Cyberpragmatics Study - Pramujiono, Agung; Rohmah, Nur; Hanindita, Amelia Widya; Ardhianti, Mimas (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Indonesian internet users (Netizens) are considered uncivilized in using the internet. The Digital Civility Index (DCI) states that the politeness of Indonesian netizens was ranked 29th out of 32 countries and the worst in Southeast Asia. The uncivility of netizens is closely related to the use of emotive language, so it is necessary to study the use of emotive language by netizens. The emotive language of Indonesian netizens in responding to YouTube posts is very interesting to study from a cyberpragmatic perspective. Cyberpragmatic studies are the use of language and communication in a digital environment or in cyberspace. The problems studied in this study are formulated: (1) How is the lingual form of the emotive language of Indonesian netizens realized in responding to YouTube posts in a cyberpramatic perspective? And (2) How is the emotive language function of Indonesian netizens realized in responding to YouTube posts in a cyberpramatic perspective? The purpose of this study is to describe and explain the realization of the form of Indonesian netizen emotive language and the function of netizen emotive language in responding on YouTube posts. This research is a descriptive qualitative research. The research data is in the form of netizens' verbal responses to internet-mediated YouTube posts as a field for cyberpragmatic studies. Data was collected using the Simak Bebas Libat Cakap (SBLC) technique. Data analysis was carried out using descriptive techniques using the interactive model Miles and Huberman (1992) with the stages of data collection, data reduction, data presentation, and verification/drawing conclusions. Based on the results of data analysis, it was concluded that the lingual form of emotive language is stated in utterances in declarative, interrogative, and directive modes, while the function of emotive language is stated in delarative speech acts with the function of stating, informing, confirming, giving advice, and praying; in expressive speech acts with functions of praising, expressing pleasure, expressing pride, thanking, apologizing, satirizing, mocking, and insulting; in imperative speech acts with functions of ordering, prohibiting, inviting, and asking. The conclusion of this study is that the lingual form of emotive language is realized in speech in declarative, interrogative, and directive modes.